Pendidikan Anak Usia Dini dalam Keluarga di Era Disrupsi Berdasarkan 2 Timotius 3:15-17 - Meilani Meilani; Andreas Fernando (Shalom: Jurnal Teologi Kristen, 2021)
Abstract: Technological developments that occur massively have made children grow up in a different pattern from the previous generation who lived in the past. Children from an early age have been acquainted with technology that affects their cognitive development and behavior patterns. The purpose of writing this article is to find out the theory and practice of family education that is appropriate for early childhood in facing challenges in this era of disruption by looking at the content of the context of 2 Timothy 3:15-17. The method used in this research is descriptive qualitative. The data collection technique was by examining the theological descriptions of 2 Timothy 3:15-17 from the Bible, as well as digging up information from various literatures, in the form of journals, commentaries, and books on early childhood development and the era of disruption. Through this research, it was found that based on 2 Timothy 3:15-17, the best way to educate children in today's families is to educate them as early as possible to study and explore the contents of the Holy Scriptures so that children have wisdom in overcoming problems and challenges, especially those that can shake faith as a result. the impact of current technological advances.   Abstrak: Perkembangan teknologi yang terjadi secara pesat saat ini telah membuat anak-anak bertumbuh dengan pola yang berbeda dari generasi yang hidup pada masa sebelumnya. Anak sejak usia dini telah berkenalan dengan teknologi yang memengaruhi perkembangan kognitif dan pola tingkah laku mereka. Tujuan dari penulisan artikel ini adalah untuk mengetahui teori dan praktik pendidikan keluarga yang sesuai bagi anak usia dini dalam menghadapi tantangan di era disrupsi ini dengan melihat isi konteks dari 2 Timotius 3:15-17. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Teknik pengumpulan data dengan mengkaji uraian teologis dari 2 Timotius 3:15-17 dari Alkitab, juga menggali informasi dari berbagai literatur, berupa jurnal, buku-buku tafsiran, dan buku-buku mengenai perkembangan anak usia dini dan era disrupsi. Melalui penelitian ini ditemukan bahwa berdasarkan   2 Timotius 3:15-17, cara terbaik pendidikan anak dalam keluarga masa kini adalah dengan sedini mungkin mendidik mereka untuk mempelajari dan mendalami isi Kitab Suci sehingga anak memiliki hikmat dalam mengatasi masalah dan tantangan terutama yang dapat menggoyahkan iman akibat pengaruh kemajuan teknologi saat ini.